Rehabilitation therapists perceptions of telehealth services in Cyprus and Greece - Papasalourou, Efstathia – Nefeli (Department of Rehabilitation Sciences, Faculty of Health Sciences, Cyprus Universtiy of Technology, 2020)
The COVID-19 pandemic brought telehealth into focus as a potential and alternative model of service provision, which facilitates therapists to provide services without the need of direct in person contact. However, as a novel service delivery model, some clients and healthcare professionals have reservations about telehealth and as such, this method of care is not being utilized to its fullest potential. The purpose of this study is to fill the gap in the literature and to provide insight regarding rehabilitation therapists‟ experiences and perceptions about the strengths and barriers of telehealth as a service model in Cyprus and Greece. 110 Greek-speaking rehabilitation therapists participated in this survey study. The results indicate what therapists view as benefits and barriers of telehealth. In addition, the results point out the issues and concerns therapists have when it comes to telehealth as a service delivery model and potential strengths, weaknesses and solutions to challenges that can be implemented in future programs. This is essential to continue to expand occupational therapy, speech and language therapy and physiotherapy outreach services in children and across various populations via a virtual context in Cyprus and Greece.
Keywords: Telehealth; Rehabilitation therapists; Service delivery model; Cyprus; Greece; COVID-19